Liquidation of the Government Protection Bureau, creation of the State Protection Service - Ura, Elżbieta (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The aim of the article is to draw attention to the basic issues related to the functioning of the newly created State Protection Service in place of the Government Security Bureau that had been operating so far. The reasons for creating a new formation, which were included in the explanatory memorandum of the bill, were also presented. The attention was paid to the powers to conduct operational and reconnaissance actions, which were granted to the new formation. In addition, it was mentioned that the regulations allowing for the termination of the official relations of the officers and employees of the Government Protection Bureau had been adopted if they had not received an offer of further service or work.